The Prospect Of ASEAN Migration Governance - Yazid, Sylvia; Septiyana, Iyan (RMPI-BRIN, 2019)
ASEAN member countries are migrant-sending and receiving countries. Around 7.3 million ASEAN citizens are migrant workers, more than 740 thousand refugees are from Myanmar, and many ASEAN citizens are victims of human trafficking. Frequently, these migrants get discriminatory treatment, which makes them unable to fulfil their human rights. ASEAN, as a regional organization, is an actor that can implement migration governance in the region. As a governance institution, ASEAN has several migration instruments relating to human trafficking and migrant workers. To implement this regional instrument, ASEAN forms bodies that function to encourage and protect migrant rights. The Rohingya people from Myanmar still experiences forced migration and displacement. However, ASEAN still does not have a comprehensive instrument that can be a source of regional governance toward the issue. This paper will discuss the prospects of ASEAN migration governance in resolving migration issues in the region.